The Effect of Compensation, Transformational Leadership on Work Engagement by Mediating the Behavior of Organizational Citizens in Insurance Broker Companies - Kacaribu, Hendri; Baskara, Ika (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This study examines the factors that influence Work engagement in the insurance brokerage industry in Indonesia, where Compensation, transformational leadership are the independent variables, while Organizational Citizen Behavior is the mediation. The sample used was 360 respondents, collected through a questionnaire and measured with a 1-5 Linkert scale and analyzed using Structural Equation Modeling (SEM). This study found that Compensation, transformational leadership has a positive effect on Organizational Citizen Behavior in insurance brokerage companies, while Compensation, transformational leadership has a positive effect on Work engagement in insurance brokerage companies. Organizational Citizen Behavior also influences work engagement in insurance brokerage companies. In addition, this study also shows the results of the influence of Organizational Citizen Behavior mediation on the positive relationship of Compensation, transformational leadership on Work engagement in insurance brokerage companies. For future researchers, it is expected to add other factors that influence work engagement as well as industry and other analysis in order to add research insight. This research has implications for insurance brokerage companies to consider Compensation, transformational leadership, Organizational Citizen Behavior in order to be able to increase work engagement so that insurance brokerage company goals can be achieved effectively and well as expected. In addition, it is necessary to examine in more detail the relationship between Organizational Citizen Behavior and Work engagement in insurance brokerage companies in Indonesia.